Obstetric bleeding complications - Pfanner, G.; Kilgert, K. (Hämostaseologie, 2006)
The instability of the gestational and puerperal equilibrium of haemostasis is affected by a shift of primary and plasmatic haemostasis in a procoagulatory direction, whereas the regulation mechanism of the fibrinolytic system can easily cause disproportional peri- and postpartal reaction leading to massive haemorrhage. Peripartal injuries or an atonic uterus can lead to massive haemorrhage and cause a classic haemorrhagic coagulopathy. Complications like amniotic fluid embolism, puerperal sepsis, eclampsia or HELLP syndrom can lead through DIC to rapidly developing and possibly fulminant hyperfibrinolysis.This article depicts different forms of haemorrhage in the peripartal situation, their particular pathologies and specific possibilities for management. A case study demonstrates the diagnostic and therapeutic options in the case of eclampsia with early abruption of placenta.
Keywords: Obstetrics; coagulation management; hyperfibrinolysis; DIC